Investigation of Confinement Effects for Determining Moment Curvature and Interaction Diagram of Reinforced Concrete Column - Bhusal, Bikram; Paudel, Satish; Katuwal, Tek Bahadur (Technical Journal, 2020)
This paper presents the relevance of using various material models to represent the inherent material non-linearity of the cross-section in generating moment curvature relationship. Further, confinement effects are imposed on geometry and P-M diagram is constructed of typical cross-section of column adopted in Nepal. Also, the modelling capability and user defined modelling aspects in terms of section, material behavior is assessed and suitability of modelling criteria to depict the actual displacement capacity is studied. It was observed the ultimate curvature of the un-confined concrete section considered was obtained approximately to be 0.16 per m while for studied confined material models the curvature was obtained approximately to be 0.66 per m. This increase in curvature is due to the confinement effect of the lateral ties. It was observed that the loss of strength of concrete in cover is compensated by use of the confinement since gain in axial and bending capacity of the confined concrete in comparison to unconfined one in compression control region. Hence, it is suggested to adopt the confined material model as user-defined for generating hinge property for non-linear analysis of the structures.